„Święte życie” na Lizbońskiej. Architektura i sacrum w poezji Mirona Białoszewskiego - Grądziel-Wójcik, Joanna (Poznańskie Spotkania Językoznawcze, 2015)
The article presents the late authorship of Miron Białoszewski, especially his poems collected in the book Odczepić się (1978) and a diary Chamowo (2009) that are a document of the poet’s life in the block of flats after his removal to the flat in a tower block at the Lizbońska Street in Warsaw in 1975. In these texts we may notice the new way of writing that was formed by new accommodation and living arrangement that influenced the poets’ life. On the other hand the room on the ninth floor occurs the place that was marked with sacrum and it puts an impact on the poets’ metaphysical and supernatural experience. The flat in the tower block has also influenced the author’s perspective and the way of writing, so that Białoszewski has experienced terminal situation – being between the two forms of living, balancing between the earth and heaven, profanum and sacrum. The removal starts to resemble a ferry across Styx, and the ninth floor becomes an unwanted porch of eternity. The titled word odczepianie się (disconnecting, separating) from the past and being at the top of the tower block means the new beginning for the poet, and writing becomes an imitation of the God’s act of creation that helps Białoszewski to accommodate in the world after heart attack and removal.